The clinical, immunological and microbiological impact of the 10-valent pneumococcal-Protein D conjugate vaccine in children with recurrent protracted bacterial bronchitis, chronic suppurative lung disease and bronchiectasis: A multi-centre, double-blind, randomised controlled trial - Kerry-Ann F. O'Grady; Anne B. Chang; Allan Cripps; Edward K. Mulholland; Heidi Smith-Vaughan; Nicholas Wood; Margaret Danchin; Ruth Thornton; Andrew Wilson; Paul J. Torzillo; Peter M. Morris; Peter Richmond; et al. (Taylor & Francis Group, 2018)
We aimed to determine the efficacy of the 10-valent pneumococcal-Haemophilus influenzae protein D conjugate vaccine (PHiD-CV) in children aged 18-months to <18-years with recurrent protracted bacterial bronchitis (rPBB), chronic suppurative lung disease (CSLD) or bronchiectasis. In a multi-centre, double-blind randomised controlled trial, children received two doses, 2-months apart of the 10vPHiD-CV or quadrivalent meningococcal-ACYW135 conjugate vaccine. Active surveillance for acute exacerbations, respiratory symptoms and antibiotic use was undertaken through to 12-months after the second vaccine dose (clinical cohort only). Serum, saliva and nasopharyngeal swabs were collected to measure immunological and microbiological effects (immunology cohort). Between December 2012 and August 2015, 62 children were enrolled onto the clinical protocol (1 excluded from clinical analyses due to unblinding), while 74 contributed to the immunology cohort (overall mean age = 6.8-years (standard deviation = 3.7), 42 (56.8%) male). The absolute risk difference comparing the 10vPHiD-CV group (n = 31 children) to the MenACYW135 group (n = 30 children) for acute exacerbations was -0.5 exacerbations/100-weeks at risk (95% confidence interval (CI) -2.0, 0.9). Compared to the MenACYW135 group, children who received the 10vPHiD-CV were less likely to have respiratory symptoms in each fortnight of surveillance (incidence density ratio (IDR) 0.82, 95%CI 0.61, 1.10) and required fewer short-course (<14-days duration) antibiotics (IDR 0.81, 95% CI 0.61, 1.09). The vaccine was immunogenic and no serious adverse events related to the vaccine were reported. In conclusion, 10vPHiD-CV might have a future role in managing children with rPBB, CSLD and bronchiectasis, but larger multicentre trials are needed to confirm or refute findings from this preliminary study.